Associação entre polimorfismos genéticos nos genes DRD2, ANKK1, COMT E 5HTT com a fluorose dentária - Souza, Luíse Gomes de (2021)
Introduction: Excessive fluoride intake can lead to a defect in tooth enamel development, dental fluorosis (DF), resulting in hypomineralization and porosity in the affected tooth enamel. The aim of this study was to investigate and evaluate the association between genetic polymorphisms in the genes DRD2, ANKK1, COMT and 5HTT with DF, in a population of adolescents living in the city of Curitiba. Materials and Methods: This is a case-control study that followed the recommendations to strengthen the report on observational epidemiological studies in epidemiology (STROBE) and used a representative sample of 936 adolescents, aged between 10 and 14 years. Of these, 256 adolescents who were clinically examined were randomly selected. DF was classified as very mild, mild, moderate, and severe according to the Dean index modified by Rozier. Only permanent teeth were used to determine the presence of DF. Genomic DNA was collected by scraping the oral mucosa, extracted, and genotyped in real-time PCR. Single nucleotide polymorphisms (SNPs) were selected by consulting the International Hap Map Project website (www.hapmap.org). Two SNPs from the DRD2 gene (rs6275 and rs6276), one from the ANKK1 gene (rs1800497), two SNPs from the COMT gene (rs6269 and rs4818) and two SNPs from the 5HTT gene (rs3813034 and rs1042173) were selected. Allele, haplotype and diplotype frequency comparisons were performed using PLINK version 1.06. To identify SNP-SNP interactions, Multifactorial Dimensionality Reduction (MDR) was performed. Genotypic analysis was performed using Fisher's exact test and Poisson regression adjusted for sex. Results: From a total of 256 adolescents, 211 (82.4%) were free of DF and 45 (17.6%) individuals had DF. In allelic frequency analysis, SNP 6275 was associated with FD (p=0.040) and SNP 6276 was borderline for FD (p=0.07). In the analysis by haplotype, the result confirmed the significant difference between the control group and the group with DF in the T-G (p < 0.05) and borderline in the C-A haplotype (p = 0.06). For the DRD2 gene in the rs6275 polymorphism in the CC genotype, there was an association with fluorosis in the Fisher test (p = 0.041) and in the Poisson test (PR= 5.37; CI= 1.59 – 18.11). In addition, there was an association with the rs6276 polymorphism in the AA genotype using the Poisson test (RP= 5.10; CI=1.51 – 17.25). In the combination of the rs6275 and rs6276 polymorphisms, it was evidenced that CC + AA had a higher prevalence of DF (p = 0.007). It can also be observed that individuals with the CC genotype at rs6275 had a higher chance of very mild fluorosis and mild fluorosis in the Fisher test (p = 0.03) and using the Poisson test (p = 0.02). The same result was observed for rs6276 in the AA genotype (p=0.05). For the ANKK1, COMT and 5HTT genes and their polymorphisms, no association with FD was observed. In MDR analysis, the interaction DRD2 (rs6276), ANKK1 (rs1800497), COMT (rs4818) and 5HTT (rs1042173) act synergistically to increase the risk of FD. Conclusion: The rs6275 and rs6276 polymorphisms in the DRD2 gene are associated with DF and there is synergism between the polymorphisms of the DRD2 (rs6276), ANKK1 (rs1800497), COMT (rs4818) and 5HTT (rs1042173) gene in the manifestation of DF.